Pemanfaatan Limbah Plastik Sebagai Bahan Campuran Aspal Pada Perkerasan Aspal AC-WC Dengan Perendaman Air Tawar Dan Air Laut Secara Berulang - Poetry, Seren Adelia; Nurdin, Abd. Rahim; Yusuf, Andi Rumpang (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
Asphalt is a cementitious material, dark or dark brown pattern, with the main factor of bitumen obtained from petroleum refining residues acting as an aggregate binder in road making. The purpose of this research is to determine the effect of increasing LDPE on Marshall's characteristics in asphalt mixtures with repeated immersion. This study used LDPE plastic waste with an accumulation of 10%, 15%, and 20%. The test item samples were made of 27 variation samples. Treatment of test items was tried with repeated soaking variations of 3, 7, as well as 10 days. The manufacture of test objects is mixed hotly and refers to the 2018 Bina Marga Specifications. Testing was tried with Marshall test kits. The results of this test show that the influence of LDPE plastic waste as an added material on asphalt mixture with repeated immersion can cause density, stability, MQ, and VFB values to shrink. On the contrary, the value of flow, VMA, and VIM increases.